1997
DOI: 10.1108/eum0000000004320
|View full text |Cite
|
Sign up to set email alerts
|

Sources of effectiveness in the business‐to‐business sales organization

Abstract: The significance of the search for sales organization effectiveness is underlined by the major costs represented by the field salesforce for many organizations, and it is heightened by the pressures of global competition and new challenges to develop long‐term customer relationships as the foundation for competitive and sustainable marketing strategies. A study of sales management in British companies adds to an emerging research stream by identifying certain characteristics of superior performance and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 15 publications
10
51
0
4
Order By: Relevance
“…Similarly, the study conducted by Piercy et al, (1997) and Babakus et al, (1996) found a positive relationship between the technical knowledge of the sales people and their outcome performance for an organization effectiveness. Weitz (1981) defined the adaptive selling as the sales person's ability to alter his/her sales behavior when interacting with customers.…”
Section: Sales Force Effectivenessmentioning
confidence: 77%
“…Similarly, the study conducted by Piercy et al, (1997) and Babakus et al, (1996) found a positive relationship between the technical knowledge of the sales people and their outcome performance for an organization effectiveness. Weitz (1981) defined the adaptive selling as the sales person's ability to alter his/her sales behavior when interacting with customers.…”
Section: Sales Force Effectivenessmentioning
confidence: 77%
“…Hal ini ditunjukkan dari nilai mean variabel Kinerja Sumber Daya Manusia sebesar 3.52 (1 ≤ mean ≤ 5 ), terutama penilaian responden terhadap Kemampuan memahami produk yang dibutuhkan nasabah (Ksdm1) dengan mean = 3.66 ; Evaluasi dan monitoring kepada nasabah jika kualitas produk ada yang tidak memuaskan (Ksdm3) dengan mean = 3.62 serta Kemudahan untuk dihubungi berkaitan dengan permasalahan nasabah dan penyampaian informasi yang positif (Ksdm4) dengan mean = 3.61. Dalam bisnis asuransi, di mana peranan agen sebagai tenaga penjualan dapat memberikan pengaruh terhadap kinerja perusahaan (Williams dan Attaway, 1996;Piercy et al, 1997).…”
Section: Pengaruh Kinerja Sumber Daya Manusia Terhadap Citra Perusahaanunclassified
“…The findings of the study show that the behaviour control philosophies are related to satisfaction, commitment, adherence to company policy, acceptance of authority, teamwork and review, a lack of extrinsic motivation, a greater interest in serving the agency, participative decision making, less use of pay as a control mechanism and an innovative and supportive culture. Piercy et al (1997) found most effective sales organizations have salespeople with high levels of motivation, customer orientation, team orientation and sales support orientation. They also feel loyal to the company.…”
Section: Characteristicsmentioning
confidence: 99%
“…These results suggest that behaviour based salesforce control system is more positively associated with sales organization effectiveness because the fixed salary of firms in the sample was 90% of the total compensation which is more representative of behaviour based control system. Piercy et al (1997) measured effectiveness of the sales organization in comparison with each company's major competitor and sales unit's objectives using dimensions of sales volume, market share, profitability and customer satisfaction. According to their study, the important characteristics of the most effective organizations are as follows: (1) Salesforce compensation; the most effective sales organizations pay fixed salaries in the range of 75-95 percent of total compensation.…”
Section: Review Of Studies Sales Organization Effectivenessmentioning
confidence: 99%